STRUCTURAL ASPECTS OF INFLATIONARY PROCESSES - T. I. Gordievich; P. V. Ruzanov (Вестник СибАДИ, 2018)
The article presents the structural analysis of the Russia inflation in 1992 – 2017 according to Rosstat with the focus on the latest phase of development  in terms of the economical sanctions. The inflation is heterogeneous in its  structure, because of the different degree of elements’ coverage in the  economical system and because of the diverse role of each sector in the  reproduction process. Mechanisms and factors of pricing in various sectors of economy have individual features, and the price ratio between them varies according to changing power of inflation. In this content inflation can classified as systemic and local, balanced and unbalanced. The sector of  inflation can be determined as drivers and outsiders of rising prices. In case  of systemic inflation of the price process, structural parts of the system  would be included. Balanced inflation occurs when the growth equality rates of the final products and rate of prices’ growth would be presented. Price  movement through phases of growth and decline forms a sector with minimum and maximum prices.